Transactions on aspect-oriented software development X - Leavens, Gary T. (Lecture notes in computer science, 2013)
The LNCS journal Transactions on Aspect-Oriented Software Development is devoted to all facets of aspect-oriented software development (AOSD) techniques in the context of all phases of the software life cycle, from requirements and design to implementation, maintenance and evolution. The focus of the journal is on approaches for systematic identification, modularization, representation and composition of crosscutting concerns, i.e., the aspects and evaluation of such approaches and their impact on improving quality attributes of software systems. This volume, the 10th in the Transactions on Aspect-Oriented Software Development series, contains revised, extended versions of the top five papers presented at AOSD 2012. The topics covered include debugging, analysis of software product lines, distributed software architectures, and empirical study of language support for software evolution.